Secretome analysis identifies potential virulence factors of Diplodia corticola, a fungal pathogen involved in cork oak (Quercus suber) decline - Fernandes, Isabel; Alves, Artur; Correia, António; Devreese, Bart; Esteves, Ana Cristina (Fungal Biology, 2014)
The characterisation of the secretome of phytopathogenic fungi may contribute to elucidate the molecular mechanisms of pathogenesis. This is particularly relevant for Diplodia corticola, a fungal plant pathogen belonging to the family Botryosphaeriaceae, whose genome remains unsequenced. This phytopathogenic fungus is recognised as one of the most important pathogens of cork oak, being related to the decline of cork oak forests in the Iberian Peninsula. Unfortunately, secretome analysis of filamentous fungi is limited by the low protein concentration and by the presence of many interfering substances, such as polysaccharides, which affect the separation and analysis by 1D and 2D gel electrophoresis. We compared six protein extraction protocols concerning their suitability for further application with proteomic workflows. The protocols involving protein precipitation were the most efficient, with emphasis on TCA–acetone protocol, allowing us to identify the most abundant proteins on the secretome of this plant pathogen. Approximately 60 % of the spots detected were identified, all corresponding to extracellular proteins. Most proteins identified were carbohydrate degrading enzymes and proteases that may be related to D. corticola pathogenicity. Although the secretome was assessed in a noninfection environment, potential virulence factors such as the putative glucan-β-glucosidase, neuraminidase, and the putative ferulic acid esterase were identified. The data obtained forms a useful basis for a deeper understanding of the pathogenicity and infection biology of D. corticola. Moreover, it will contribute to the development of proteomics studies on other members of the Botryosphaeriaceae.
Keywords: 2D-electrophoresis; Botryosphaeriaceae; Filamentous fungi; Plant pathogen; Quercus suber

Evaluation of amplified ribosomal DNA restriction analysis as a method for the identification of Botryosphaeria species. - Alves, Artur; Phillips, Alan J. L.; Henriques, Isabel; Correia, António (FEMS microbiology letters, 2005)
The polymerase chain reaction was used to amplify a rDNA fragment containing the internal transcribed spacers (ITS1-5.8S-ITS2) and the D1/D2 variable domains of the 28S rDNA from 10 species of the genus Botryosphaeria (Fungi, Ascomycota). Restriction analysis of the amplicons with frequent-cutting endonucleases (amplified ribosomal DNA restriction analysis) allowed the definition of 12 rDNA haplotypes. Each of the rDNA haplotypes could be unambiguously assigned to a single Botryosphaeria species, thus allowing clear identification of all the species tested. Intraspecific polymorphism was very low and detected only in Botryosphaeria parva and Botryosphaeria dothidea. Cluster analysis of banding patterns of the isolates corresponded well with known species delineations. The method described in this paper provides a simple and rapid procedure for the differentiation and identification of Botryosphaeria isolates at the species level.
The following values have no corresponding Zotero field: accession-num: 15837376
Keywords: ARDRA; Botryosphaeria; D1/D2 domains; ITS; rDNA; Species identification

Evaluation of amplified ribosomal DNA restriction analysis as a method for the identification of Botryosphaeria species. - Alves, Artur; Phillips, Alan J L; Henriques, Isabel; Correia, António (FEMS microbiology letters, 2005)
The polymerase chain reaction was used to amplify a rDNA fragment containing the internal transcribed spacers (ITS1-5.8S-ITS2) and the D1/D2 variable domains of the 28S rDNA from 10 species of the genus Botryosphaeria (Fungi, Ascomycota). Restriction analysis of the amplicons with frequent-cutting endonucleases (amplified ribosomal DNA restriction analysis) allowed the definition of 12 rDNA haplotypes. Each of the rDNA haplotypes could be unambiguously assigned to a single Botryosphaeria species, thus allowing clear identification of all the species tested. Intraspecific polymorphism was very low and detected only in Botryosphaeria parva and Botryosphaeria dothidea. Cluster analysis of banding patterns of the isolates corresponded well with known species delineations. The method described in this paper provides a simple and rapid procedure for the differentiation and identification of Botryosphaeria isolates at the species level.
Keywords: ARDRA; Botryosphaeria; D1/D2 domains; ITS; rDNA; Species identification